Temple of swoon [large type] - Segura, Jo (Thorndike Press large print top shelf., 2025)
"While her mentor may be the world's most badass archaeologist, the only thing bad about Dr. Miriam Jacobs are her corny jokes. But when Miri is charged with leading an unmapped expedition through the Amazon for the fabled Lost City of the Moon, she finally has her chance to prove to her colleagues that she's capable--and hopefully prove it to herself, too. Journalist Rafael Monfils has joined the archaeological team to chronicle their search for the lost city. Or at least, that's what they think he's doing. Rafa's real goal? Make sure the team does not reach the Cidade da Lua, stopping the desecration of the holy city and protecting his mother's legacy. All he needs to do is keep them on the wrong path. If only the endearingly quirky Dr. Jacobs wasn't so damn tenacious--each of Rafa's tricks and purposeful wrong turns only seem to fuel her determination. Even worse, he's charmed by her goofy attempts to channel Lara Croft as they traverse the dangerous Brazilian rainforest. But they're not the only crew hunting for the lost city, and soon the untamed jungle--and their untamed hearts--might be the least of their worries..."--